Measures of agri-food system gross domestic product (AgGDP+) and employment (AgEMP+) - CGIAR Research Program on Policies, Institutions, and Markets (2019)
The indicators of the size of agri-food system GDP and employment developed by PIM are used by USAID as high-level indicators for tracking progress in implementing USAID's Global Food Security Strategy for 2018-2024. IFPRI researchers worked with USAID staff to develop the indicators and draft country briefs.